Experimental assessment of hybrid binary and ternary fuel blends on CI engine performance, emissions, and combustion characteristics - Fareed, Aisha F.; El-Shafay, A. S.; Gad, M. S.; Agbulut, Umit (SPRINGER, 2025)
The increased density and viscosity of crude biodiesel derived from palm and waste cooking oils (WCO) present problems such as vaporization and atomization. A hybrid biodiesel mixture ensures to have better calorific values, lowest density, and viscosity. Biodiesel fuels were synthesized using the esterification and transesterification of palm and WCO, and it was blended in proportions of 10 and 20% with pure diesel. Combustion, performance, and emissions of diesel engine fuelling with hybrid biodiesel blends at load variation and rated speed of 3000 rpm were evaluated. Thermal efficiency was decreased with the increasing ratio of methyl ester in mixtures, whereas specific fuel consumption rose due to the diminished calorific value of methyl ester. In comparison with diesel fuel, biodiesel from palm (10%), waste cooking oil (10%), blended WCO (10%) + palm (10%), waste cooking oil (20%), and palm oil (20%) exhibited the most significant increases in specific fuel consumption, recorded at 1.5, 3.5, 6, 7, and 9%, respectively. Nonetheless, there were concomitant reductions in thermal efficiency of 2, 4, 5.5, 6.5, and 10%. Maximum reductions in smoke concentration for P10, W10, W10 + P10, W20, and P20 were 5, 7, 9, 10, and 12%, respectively. Maximum cylinder pressures were reduced by 1, 1.8, 2.8, 3.5, and 4%, on average, although the peak HRR regarding diesel fuel at maximum output power was dropped by 1, 2, 3.2, 4, and 4.5%. Hybridization of feedstocks with diverse properties improves performance, combustion, and emissions of diesel engines run by combinations of 10% palm and 10% WCO hybrid biodiesel. As an alternative fuel, hybrid palm and waste cooking methyl esters can be used to increase performance and combustion while lowering exhaust emissions.
Keywords: Waste cooking oil; Palm oil; Hybrid biodiesel; Performance; Emissions; Combustion characteristics; BIODIESEL PRODUCTION; CASTOR-OIL; FEEDSTOCKS; WASTE; PALM; Thermodynamics; Chemistry